Industrial scale suspension culture of living cells - Meyer, Hans-Peter; Schmidhalter, Diego R. (Weinheim, Germany : Wiley Blackwell, 2014)
The submersed cultivation of organisms in sterile containments or fermenters has become the standard manufacturing procedure, and will remain the gold standard for some time to come. This book thus addresses submersed cell culture and fermentation and its importance for the manufacturing industry. It goes beyond expression systems and integrally investigates all those factors relevant for manufacturing using suspension cultures. In so doing, the contributions cover all industrial cultivation methods in a comprehensive and comparative manner, with most of the authors coming from the industry.
1.3.6.1 Batch Phase for the Accumulation of Biomass1.3.6.2 Structured Approach Towards Batch Design; 1.3.6.3 Fed-Batch Phase Process Design from Scratch; 1.3.6.4 Induction Phase: Product Formation Characteristics; 1.3.6.5 Process Parameters Impacting Recombinant Product Formation; 1.3.6.6 Concept of Time-Space Yield; 1.4 Basic Bioreactor Design Aspects; 1.4.1 Introduction; 1.4.2 Vessel Design and Construction; 1.4.3 Dimensioning; 1.4.3.1 Materials of Construction; 1.4.3.2 Surface Quality and Welding; 1.4.3.3 Nozzles and Ports; 1.4.4 Mass Transfer; 1.4.5 Cleaning in Place.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cell culture; Industrial microbiology; Biotechnology; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biotechnology; Cell culture; Industrial microbiology; Gene Expression; Genetic engineering; Electronic books; Electronic books